FIGURATIVE LANGUAGES USED IN ROBERT FROST’S SELECTED POEMS - Khairunnisa, Esa; Iskandar, Iskandar (Faculty of Languages and Literature, Universitas Negeri Makassar, 2022)
Figurative language is a language that increases the beauty of a literary work, shortens the author's narrative and it could create a certain feeling and atmosphere. Those characteristics were difficult to understand for people who learn or read a poem. The researcher examined the figurative language in Robert Frost's selected poem entitled Into My Own, Stars, Reluctance, The Vantage Point, and A Prayer in Spring which has never been studied before, both figurative languages and the messages in the poem The purpose of this research is to find out the types of figurative languages and the messages expressed through figurative language in each of Robert Frost's selected poems. This study used the descriptive qualitative method. The theories used in this research are figurative language theory by Lawrence Perrine and message theory by several experts and sources. Types of figurative languages found were simile, personification, apostrophe, synecdoche, metonymy, symbol, hyperbole, and understatement. The most commonly used is personification. The messages reveal from figurative languages in the poems are: fight our fear of success, what we get is what we do, God is all-wise, nature can heal us, and ask God for everything.